Structural break, US financial crisis and macroeconomic time series: evidence from BRICS economies. Issue 3 (3rd July 2019) - Kalsie, Anjala; Arora, Ashima
Abstract: This paper analyses the overall trend of key macroeconomic variables of BRICS nations impacted by the US financial crises (2008–2009) through structural break analysis for period 2000–2013. Dummy variable model using exogenous break-date examines intercept and trend shift simultaneously in a single linear equation. The analysis statistically establishes that different variable of the countries endured varying level (severity) of the crisis impacted. Results found both immediate and lagged manifestation of the crisis impact on variables. The study's exclusivity lies in exposing the exact period of crisis impact on each variable and also in capturing their exact trend movements. The paper contributes in isolating sensitive variables (sensitive/resilient to exogenous shocks) for further research on crises.